FeCrAlloy monoliths coated with Ni/Al2O3 applied to the low-temperature production of ethylene - Brussino, Paula (2018)
This paper investigates the oxidative dehydrogenation of ethane to produce ethylene at low temperatures (500°C) in metallic structured substrates. To check this point, the FeCrAlloy® monoliths with different channel sizes (289 - 2360 cpsi) were prepared. The monoliths were coated with a Ni/Al2O3 catalyst (by washcoating of alumina and the latter nickel impregnation) and characterized by Scanning Electron Microscopy and Energy-Dispersive X-ray analysis (SEM-EDX), Temperature-Programmed Reduction (TPR), X-ray Diffraction (XRD) and X-ray Photoelectron Spectroscopy (XPS). The catalytic results showed that all monoliths coated with ~300 mg of catalyst presented similar ethane conversion (15%) at  450°C. However, the lowest selectivity to ethylene was found for the monolith with the lower channel size and the higher geometric surface area, where a heterogeneous catalyst layer with Ni enriched islands was generated. Therefore, it can be said that the selectivity to ethylene is linked to the distribution of Ni species on the support (alumina). Nevertheless, in all cases the selectivity was high (above 70%). On the other hand, the stability in reaction tests of one of the coated monoliths was done. This structured catalyst proved to be more stable under reaction conditions than the powder catalyst, with an initial slight drop in the first 8 h but after that, constant activity for the 152 h left.